The Influence of Performance Allowances on Employee Work Motivation at the Office of the Ministry of Religion of East Tanjung Jabung Regency - Lestari, Puji; Abidin, Zaenal; Nilfatri, Nilfatri (CV. Zabags Qu Publish, 2023)
The author is interested in conducting this research because based on the observations of researchers that occurred at the Office of the Ministry of Religion of East Tanjung Jabung Regency, the employees still lack high work motivation, it can be seen that there are still some employees who arrive late and return late after lunch break. This study aims to determine and analyze the effect of performance allowances on employee motivation in the Office of the Ministry of Religion of East Tanjung Jabung Regency. In this study, researchers used quantitative methods with research instruments using questionnaires, namely by distributing statements by direct interviews and using the Google form. In this study, researchers used Stratified Sampling samples (level sampling). Stratified Sampling is a sampling procedure in which the target population is separated into unique and homogeneous segments (strata), and then a simple random sample is selected from each segment (stratum). With a population (N) of employees in the Office of the Ministry of Religion of East Tanjung Jabung Regency, namely as many as 34 employees. Data were analyzed using descriptive statistics, validity test, reliability test and simple regression test (t test) using the Microsoft Excel 2007 application and the SPSS version 25 application for windows. The results of this study indicate that performance allowances have an influence on work motivation and the magnitude of the effect of performance allowances on employee work motivation in the Office of the Ministry of Religion of East Tanjung Jabung Regency is 3.7%.